Crude Oil Prices and Currency Exchange Rates’ Impact on the Indonesian Energy Stock Market during the Covid-19 Pandemic - Mohammad Benny Alexandri; Putri Irmala Sari; Widya Setiabudi Sumadinata (International Journal of Energy Economics and Policy, 2022)
This study examines the effect of oil prices and currency exchange rates on the Indonesian Energy Stock Market, which was listed on the Indonesian Stock Exchange from 2020 to 2022. The purpose of this study is to select samples from the entire population. This study employed the ADF and Zivot-Andrews (1992) unit root test analyses. To begin, causality between the variables was established. The data suggested that alternate fees, closing price, and trade rat are causally related. The VAR method was used to investigate the short-term effects of the variables At the same time, oil prices have a beneficial effect on closing costs, trading prices experience closing post costs and Currency Exchange Rate prices During the Covid-19 Pandemic.